Zarządzanie ryzykiem w polskich spółkach publicznych - badania empiryczne - Kuziak, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents an analysis of the risk management policy in some Polish companies listed on the Warsaw Stock Exchange. The author chose 40 companies (capitalization at least 600,000,000 PLN). The study was divided into parts consistent with risk types: interest rate risk, currency risk, credit risk, commodity risk and others. The author analyzed the risk management policy and derivatives used in the risk management process. The analysis was based on the information coming from companies financial reports. Finally, the author noticed that companies have mostly accepted the types of risk identified (interest rate risk and credit risk) but in most cases operational risk has not been identified. Currency forwards have been very often used in the hedge strategy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 225-232